Open Library of Science (OLS) - Ahmad, Umar Salisu (My University, 2022)
A slide deck of my presentation during my Graduation Ceremony at OLS-5 (Cohort of Hope), Open Life Science Program. Here, I talked about the rapidly growing of Article Processing Charges (APCs) in open access scholarly journals at the global scale, which restricted Nigerian scientists and researchers from publishing in high quality journals due to limited access to research funding. Moreover, I also shared more light on why so many Nigerian Journals are not visible online and are not even indexed in some of the indexing databases. It is due to this limitation that I provided an alternatives publishing model based on the concept from Open Library of Humanities (OLH) to solve this potential problem. I thought of this idea of developing an Open Library of Science (OLS) which aim at developing an open access publication platform (standalone and collection-based independent journals) for Nigerian academic and learned society journals to simply aid in increasing discoverability of Nigerian research output. The OLS is of course going to be a not-for-profit that will collectively be funded by a consortium of institutional libraries through paying a small subsidy fee, and possibly through Tertiary Education Trust Fund (TETFUND), an established Federal Government Agency that is funding research in all the government-owned tertiary institutions in Nigeria.
Keywords: Article Processing Charges; Open Acess publication platform; Open library of science